REACTIONS OF STRONGLY POLAR IONS WITH MOLECULES - Clary, D (1995)
A theoretical study is reported on the effect of various long-range terms in the potential energy surface on the rate constants for the reactions of strongly polar ArH3+ with H2O and NH3. A rotationally adiabatic capture theory is used. It is found that dipole-dipole, dipole-induced dipole and dispersion terms produce a small enhancement (about 18%) of the rate constant calculated with only the ion-dipole and ion-induced dipoles terms in the potential energy surface. The calculated rate constants agree very well with experiment. © 1995.